ORAL LICHENOID LESIONS AND ALLERGY TO DENTAL MATERIALS - Ditrichova, Dagmar; Kapralova, Simona; Tichy, Martin; Ticha, Vlastislava; Dobesova, Jitka; Justova, Eva; Eber, Miroslav; Pirek, Petr (Biomedical papers, 2007)
Background: Dental materials, oral hygiene products and food additives may cause contact allergic reactions in the mouth with varied clinical presentation. Oral lichenoid lesions (lichen planus-like lesions) can be induced by hypersensitivity to dental restorative metals, acrylates, flavorings and other substances.Aim: The aim of this study was to demonstrate contact allergy to dental materials in patients with oral lichenoid lesions using patch tests.Patients and methods: Routine patch tests with two sets of allergens - "European Standard" and "Dental Screening" (Chemotechnique Diagnostics, Sweden) supplemented with pulverized amalgam, iridium, indium, menthol, sorbic acid and platinum were done on a set of 25 patients with lichenoid lesions located on the buccal mucosa, tongue and lips. Application and interpretation of the tests were conducted according to ICDRG (International Contact Dermatitis Research Group).Results: 15 (60 %) patients showed sensitization to 1 or more allergens, with a total of 31 positive reactions. The greatest frequency of positive reactions was to dental metals, with a total of 27 positive reactions. The order of tested metals according to frequency of positive reactions was mercury (6/25/24 %), amalgam (6/25/24 %), nickel (4/25/16 %), palladium (4/25/16 %), cobalt (3/25/12 %), gold (2/25/8 %), chrome (1/25/4 %), indium (1/25/4 %). The clinical relevance of the results with regard to the material's presence in the mouth was demonstrated in 11 (44 %) patients. In 9 patients, replacement of the positively tested materials led to healing or to significant regression of mucosal changes.Conclusions: The results of the patch tests showed the possible contribution of contact sensitization in the pathogenesis of lichenoid manifestations in the oral cavity. Due to the premalignant character of these lesions, replacement of positively tested materials and follow up of these patients is advised.
Keywords: Oral lichenoid lesions/Patch tests/Contact allergy/Dental materials/Amalgam